2016
DOI: 10.1371/journal.pone.0158189
|View full text |Cite
|
Sign up to set email alerts
|

Unique Behavioral and Neurochemical Effects Induced by Repeated Adolescent Consumption of Caffeine-Mixed Alcohol in C57BL/6 Mice

Abstract: The number of highly caffeinated products has increased dramatically in the past few years. Among these products, highly caffeinated energy drinks are the most heavily advertised and purchased, which has resulted in increased incidences of co-consumption of energy drinks with alcohol. Despite the growing number of adolescents and young adults reporting caffeine-mixed alcohol use, knowledge of the potential consequences associated with co-consumption has been limited to survey-based results and in-laboratory hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Multiple studies have found that caffeine can possibly reduce one's ability to accurately assess the intoxicating effects of alcohol [15][16][17][18][19]. Participants who consumed alcohol mixed with energy drinks tend to report subjectively lower intoxication levels compared to those who consumed alcohol alone and with the same estimated blood alcohol concentration (eBAC) [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies have found that caffeine can possibly reduce one's ability to accurately assess the intoxicating effects of alcohol [15][16][17][18][19]. Participants who consumed alcohol mixed with energy drinks tend to report subjectively lower intoxication levels compared to those who consumed alcohol alone and with the same estimated blood alcohol concentration (eBAC) [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study on adolescent mice showed that repeated exposure to caffeine-mixed alcohol resulted in significant locomotor sensitisation, similar to chronic cocaine use [15]. Compared to alcohol or caffeine use alone, increased amounts of protein ΔFosB accumulate in the nucleus accumbens following repeated caffeine-mixed alcohol exposure [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased striatal activation during reward processing has been found in gambling disorder, binge-eating, and alcohol dependence (Potenza, 2014). Repeated consumption of caffeine-mixed alcohol causes stronger activation of the dopaminergic reward pathway than caffeine or alcohol alone (Robins, Lu, & van Rijn, 2016). Furthermore, previous studies examining neurobiological correlates of problem gambling have identified abnormalities in brain dopamine systems that are crucial for reward sensitivity (Wardell, Quilty, Hendershot, & Bagby, 2015).…”
mentioning
confidence: 99%